Akses Digital dan Status Kesehatan Masyarakat di Asia Tenggara: Studi Deskriptif di Indonesia, Malaysia, Dan Thailand - Zilfadila Zilfadila; Asmaripa Ainy (Politeknik Negeri Jember, 2023)
Internet access has become an important part of people's lives. Various digital platforms have been used to deliver health information to large populations. This study aimed to describe the health status based on digital access and sociodemographic factors of people in Southeast Asia, especially Indonesia, Malaysia, and Thailand. This study was a secondary data analysis of the World Value Survey Wave 7 (2017–2022) with a cross-sectional design. The sample in this study was the population aged 18 years and over, with a total of 2,917 respondents in Indonesia, 1,313 respondents in Malaysia, and 1,446 respondents in Thailand. The data were analyzed descriptively. Respondents in Thailand had the best health status (98.5%). Meanwhile, respondents who utilized digital access were most prevalent in Malaysia (95.4%). In all three countries, namely Indonesia, Malaysia, and Thailand, most respondents who utilize digital access have a good health status. Good health status in all three countries is dominated by male respondents, productive age, having ≤4 family members, working, being married, and having a high education level.